2010
DOI: 10.1063/1.3436568
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of thermal conductivity in nanodot nanocomposites and nanograined nanocomposites

Abstract: Thermal conductivity of nanocrystalline silicon by direct molecular dynamics simulation J. Appl. Phys. 112, 064305 (2012) Electrical and heat conduction mechanisms of GeTe alloy for phase change memory application J. Appl. Phys. 112, 053712 (2012) Thermal rectification and phonon scattering in silicon nanofilm with cone cavity J. Appl. Phys. 112, 054312 (2012) Analysis of the "3-Omega" method for substrates and thick films of anisotropic thermal conductivity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
(30 reference statements)
0
13
0
Order By: Relevance
“…In the simulation, lattice thermal conductivities of QAH and AH are similar despite the fact that they have different grain sizes and diameters of their nanostructures. It is known that phonon grain boundary scattering is usually dominant at temperatures lower than the Debye temperature (32) unless the sizes of the grains are very small, e.g., on the order of a few tens of nanometers (16). Considering that the Debye temperature of PbTe (33) is 136 K, the differences in the grains did not affect the lattice thermal conductivities significantly in the measured temperature range.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the simulation, lattice thermal conductivities of QAH and AH are similar despite the fact that they have different grain sizes and diameters of their nanostructures. It is known that phonon grain boundary scattering is usually dominant at temperatures lower than the Debye temperature (32) unless the sizes of the grains are very small, e.g., on the order of a few tens of nanometers (16). Considering that the Debye temperature of PbTe (33) is 136 K, the differences in the grains did not affect the lattice thermal conductivities significantly in the measured temperature range.…”
Section: Resultsmentioning
confidence: 99%
“…Band convergence has been suggested as another method of increasing the power factor; Pei et al (10) reported an enhancement of the figure of merit to 1.8 at around 850 K due to an optimized power factor via the convergence of at least 12 valleys in Pb 0.98 Na 0.02 Te 1-x Se x alloys. In addition, by tuning the energy separation between the three bands (C + L + Σ) to achieve an optimal carrier concentration in 2 mol % Nadoped Mg x Pb 1-x Te alloys (20), a significant enhancement of the zT over a wide temperature range was achieved, with a peak zT value of ∼1.7 at 725 K. It is now well known that nanostructures such as nanoparticles (15)(16)(17)21) and nanosized grain boundaries (18) can scatter phonons effectively, thereby reducing the thermal conductivity. Girard et al (22) reported that the Na-doped PbTe-PbS 12% formed PbS nanostructures, which reduced the lattice thermal conductivity significantly and thus achieved a maximum zT of 1.8 at 800 K. Recently, a significant enhancement of the figure of merit of 2.2 at 915 K in sparkplasma-sintered (SPS) 2% Na-doped PbTe-SrTe alloys was reported by Biswas et al (15) These authors attributed the large increase in zT to the thermal conductivity reduction achieved…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…34 According to Soffer's specularity model, if the disruption of the grain boundary is of the order of two atomic distances (i.e., g $ 1 nm), the probability of specular scattering of phonons at the grain boundaries is p < 0.013. Due to these small values for specular reflection, as done by others, 13,20 we assume in our model that phonons are diffusely scattered at the grain boundaries.…”
Section: Reduced Thermal Conductivity In Polycrystalsmentioning
confidence: 99%
“…In the literature, a large number of theoretical works have studied the conduction of heat in single crystalline thin films [8][9][10][11][12][13][14][15] but less work has been performed to understand heat transport in nano-structured polycrystalline materials. 6,[16][17][18][19][20] The understanding and control of thermal energy transport in highly efficient microelectronic devices and thermoelectric materials requires the development of theoretical approaches that can accurately describe the transport of phonons in polycrystalline semiconductor materials.…”
Section: Introductionmentioning
confidence: 99%